Prawo i wolność. Studium filozofii politycznej Borysa Wyszesławcewa - Paradowski, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
According to Wyszesławcew, the starting point of any moral reflection that would be deserving of the name is the statement that is a philosophical transposition of the Apostle’s words: evil emerges into the world accompanying law. The words should be understood quite literally – it is not that with law we develop the awareness of evil that we have already unconsciously committed. The point is that once established, the law prompts us to evil.Wyszes3awcew’s notion of law is very broad; he understands law as any ethical, customary, religious or legal norm, especially when it assumes the form of prohibition. Therefore, both the order of Moses and the ethics of the Stoics, Roman law and Kant’s categorical imperative are ominous, demoralizing laws.